2011
DOI: 10.1089/dia.2010.0255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Temperature on Analytical Performance of Self-Monitoring Blood Glucose Systems

Abstract: The effect on analytical performance was most pronounced after a rapid shift in the ambient temperature. Therefore patients need to wait at least 15 min for temperature equilibration of affected meters and strips before measuring blood glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…These sources include differences in the manufacturer's measurement procedure, 19 manufacturer-specific plasma conversion factors, but also handling errors by the users. [20][21][22][23] As another possible source of inaccuracy, we observed variability between different test strip vials inside one lot.…”
Section: Discussionmentioning
confidence: 97%
“…These sources include differences in the manufacturer's measurement procedure, 19 manufacturer-specific plasma conversion factors, but also handling errors by the users. [20][21][22][23] As another possible source of inaccuracy, we observed variability between different test strip vials inside one lot.…”
Section: Discussionmentioning
confidence: 97%
“…Conventional self-monitoring blood glucose devices have been shown to over-and/or underestimate results by at least 5% because of rapid shifts in ambient temperature. 29 The accuracy of microdialysis-based CGM devices is influenced by temperature with a 4% variation in current signal for each change in°C, 30 which may be overcome by application of a temperature-compensating algorithm. 31 Decline in pH, as occurs with the development of lactic acidosis during more intense exercise, has not been shown to affect sensor performance.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 9 SMBG systems available in Norway explored the impact of temperature changes on the accuracy of BG measurements. 35 A change from 5°C to room temperature immediately before measurement, produced upward discrepancies >5% in 4 of these SMBG systems. Conversely, after a rapid change from 30°C to room temperature, 4 of the 9 BG systems presented downward discrepancies >5%.…”
Section: Temperature and Humiditymentioning
confidence: 93%
“…Conversely, after a rapid change from 30°C to room temperature, 4 of the 9 BG systems presented downward discrepancies >5%. 35 A period of acclimatization (up to 15-30 minutes) seemed to lessen these effects. A recently published study on 5 modern BG systems showed that compensating mechanisms within the system allowed a good performance at extreme high and low temperatures.…”
Section: Temperature and Humiditymentioning
confidence: 98%